The Long-Term Impact of Maritime Piracy on Seafarers’ Behavioral Health and Work Decisions - Seyle, D Conor (Archīum Ateneo, 2017)
More than 6000 seafarers have been held hostage by pirates in the last ten years. There is a small but developing body of research showing that these seafarers may face lasting challenges in recovery. However, current studies on this question have been limited by a lack of comparison groups, a lack of statistical power, and other methodological challenges. This study contributes to this body of research through a survey of 101 former hostages and 363 seafarers not known to be exposed to piracy from India, the Philippines, and Ukraine. Using clinically validated scales for tracking lasting impact, this research finds that 25.77% of former hostages show symptoms consistent with PTSD, and that hostage experiences and other maritime traumas can have impacts on seafarer wellbeing and decisions about their career through the impact these traumas have on post-traumatic stress symptoms. Piracy Hostages PTSD Depression Seafarer wellbeing